DIGITAL TRANSFORMATION OF USED VEHICLE UMKM SHOWROOM MARKETING THROUGH TIKTOK LIVE TO OPTIMIZE SALES - Wahyono, Muhammad; Hariawan, Ferry; Afkar, Taudlikhul (Universitas Merdeka Pasuruan, 2025)
This study addresses the limited marketing strategies of used vehicle UMKM showrooms, which have largely depended on conventional promotion methods and struggled to expand their customer base. The research aimed to examine the effectiveness of TikTok Live as an innovative digital marketing tool in enhancing sales performance. A participatory approach was applied through workshops, live demonstrations, and mentoring sessions to strengthen participants’ competencies in designing, implementing, and evaluating online campaigns. Data were collected through observation, participant feedback, and transaction records before and after the program. The findings revealed significant improvements in showroom owners’ ability to utilize TikTok Live, marked by higher audience engagement and increased conversion rates. Daily transactions showed a positive trend, with broader market coverage compared to offline promotions. These results indicate that TikTok Live is not only practical and accessible but also offers sustainable opportunities for UMKM competitiveness in the digital economy. This research contributes to the growing literature on digital transformation for small enterprises by demonstrating the relevance of live-streaming platforms in boosting business resilience and sales growth.